Pengaruh Social Media Marketing terhadap Repurchase Intention dengan Customer Experience sebagai Variabel Moderasi - Alfina Mutiara Harunnisha; Dwi Mulyaningsih, Hendrati; Dwi Nugraha, Yudha (UNISBA Press, 2024)
Abstract. This research focuses on the variables Social Media Marketing, Customer Experience and Repur-chase Intention. The aim of this research is to determine the influence of social media marketing on repurchase intention which is moderated by customer experience among Korean skincare users. The method used is a survey method and data collection tech-niques using a questionnaire distributed via Google Form. The object of this research was 150 Korean Skincare users in the city of Bandung, who were narrowed down again based on sampling criteria to 140 people. The sampling technique in the research used Nonprobability Sampling with Purposive Sampling technique. There are two hy-potheses in the research which were tested using a simple linear regression approach and Moderated Regression Analysis (MRA). The research results show that there is a positive and significant influence between the Social Media Marketing variables on Repurchase Intention among Korean Skincare users. Furthermore, the Customer Expe-rience variable does nott strengthening the relationship between Social Media Market-ing and Repurchase Intention among Korean Skincare users. Abstrak. Penelitian ini berfokus kepada variabel Social Media Marketing, Customer Experience dan Repurchase Intention. Tujuan dari penelitian ini ialah untuk mengetahui Pengaruh Social Media Marketing terhadap Repurchase Intention yang dimoderasi oleh Custom-er Experience pada pengguna Skincare Korea. Metode yang digunakan ialah metode survei dan teknik pengumpulan data menggunakan kuesioner yang disebar melalui Google Form. Objek penelitian ini adalah pengguna Skincare Korea di kota Bandung berjumlah 150 orang yang dikerucutkan kembali berdasarkan kriteria sampling menjadi 140 orang. Teknik sampling dalam penelitian menggunakan Nonprobality Sampling dengan teknik Purposive Sampling. Terdapat dua hipotesis dalam penelitian yang diuji menggunakan pendekatan regresi linier sederhana dan Moderated Regression Analysis (MRA). Hasil penelitian menunjukan bahwa terdapat pengaruh positif dan signifikan antara variabel Social Media Marketing terhadap Repurchase Intention pada pengguna Skincare Korea. Selanjutnya, variabel Customer Experience tidak memperkuat hub-ungan antara Social Media Marketing terhadap Repurchase Intention pada pengguna Skincare Korea.